PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN KOMITMEN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN PAMEKASAN - jurnalmap map; Akhmad Sukrisno; Muninghar ÔÇì; Fatimah Riswati (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT This research was conducted in Pamekasan Regional Secretariat with total sample of 64 respondents. The purpose of this study is: 1) To know the Style of Leadership, Work Discipline and Work Commitment simultaneously have an effect on Employee Work Achievement, 2) To know the style of Leadership, Work Discipline and Work Commitment partially have an effect on Employee Work Achievement, 3) To know the Style of Leadership, Work Discipline and Work Commitment which has a dominant influence Employee Work Achievement. The results showed: 1) simultaneously Leadership Style, Work Discipline and Work Commitment have a very significant influence on the performance of members, 2) Partially, Leadership Style, Work Discipline and Work Commitment have a significant influence on Employee Work Achievement in General Section of Regional Secretariat of Regency of Pamekasan, 3) job commitment variables have a dominant influence in affecting Employee Work Achievement In General Section Pamekasan Regional Secretariat. Keywords: Leadership Style (X1), Work Discipline (X2), Working Commitment (X3) And Employee Performance (Y).